PENGARUH CELEBRITY ENDORSER DAN PUBLIC RELATION TERHADAP CITRA PERGURUAN TINGGI SWASTA DAN MINAT KULIAH DI POLITEKNIK LP3I JAKARTA - Arief Rahman Arief Rahman (NIAGARA Scientific Journal, 2016)
This thesis was conducted to determine the influence Celebrity Endorser and Public Relations of the Image and Intention to Buy Private University, by giving questionnaires to students of Level III in Polytechnic LP3I Jakarta with a total population of 1527 students and samples taken 100 number of students. In this evidence using research methods by questionnaire distributed to respondents (students) as way to collecting of information about the research. Methods of statistical analysis supported by Lisrel application version 18.72, to determine the validity and reliability, the classic assumption test and doubled linear regression analysis test, path coefficients and T test to test the hypothesis necessary. The results of this research proven there is influence between Celebrity Endorser and Public Relations to imaging of Polytechnic LP3I Jakarta so that Hypothesis (Ha1) is accepted, there is influence between Celebrity Endorser and Public Relations to Intention to Buy Polytechnic LP3I Jakarta so that Hypothesis (Ha2) accepted. There is influence between Celebrity Endorser (X1) and Public Relations (X2) simultaneously to the imaging and Intention to Buy in Private University so that Hypothesis (Ha3) accepted. Whereas, the coefficient of determination (R2) of 0.99 or 99%. It means that 99% of the dependent variable is Imaging and Intention to Buy can be explained by the independent variables is Celebrity Endorser and Public Relations.